Analysis of tourism safety and its influence on tourist demand in the natural tourist attrations of Montufar canton - Chandi Yépez, Alonso Javier; Hidalgo Aguirre, C´ésar Ariel; Toapanta Ulcuango, Dennise Pamela; España Quistanchala, Anddy Nicolas (Tierra Infinita, 2022)
The research consisted of conducting an analysis of tourism safety in the canton of Montufar. The problem that was identified was the scarce analysis of tourist safety in the canton causing a deficient development of safety plans generating a limited tourist demand, for the study the following objectives were set: to diagnose the current situation of tourist safety in the canton Montufar, to determine the tourist demand in the natural tourist attractions of the canton and to establish the correlation between safety and tourist demand. The bibliographic, fundamental theoretical and correlational research methods allowed arguing relevant aspects of the research, in addition to the techniques and instruments such as: surveys, interviews applied to 205 tourists who visited the three natural tourist attractions: arrayanes forest, paluz waterfall and salado lagoon, as well as representatives of the cantonal GAD, national police and eight tourist service providers. The program used for data analysis was SPSS, which established that 90.7% of visitors have not been victims of insecurity at destinations, 83.9% rated tourist establishments as safe, 52.7% consider that the safety of a destination influences their choice of visit and 97.1% consider that tourism safety influences their choice of visit. This is corroborated by the application of the Chi-square statistic, the value of the result is less than the critical or significance value, therefore, tourism safety in Montufar canton does influence the demand of tourists.